Penggunaan Teknologi Untuk Memajukan Kreativitas Masyarakat Kontemporer Dalam Sektor Menstabilkan Perokonomian - Dina Mardiana; Eka Putri Qomaria (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In this day and age, we are no strangers to technology where this is very common among people in the world. In this process of globalization, which is increasingly increasing, it can cause changes in people's mindsets. Ordinary people who initially did not know what technology was, now everyone knows. The world which is surrounded by globalization can change the way of thinking of ancient society to become modern, where this can bring positive and negative sides. The negative side because of the development of globalization that gave rise to this technology is none other than the existence of social media content that is inappropriate for people or children to display on their social media homepages. And the positive side with this technology is that it can express people's creativity to be uploaded on social media, this can be seen from an economic perspective that can generate money. like selling ideas posted on social media, a YouTuber, etc.